LINGUOCULTURAL ASPECTS IN SOMATIC PHRASEOLOGICAL UNITS OF THE UZBEK LANGUAGE (TAMADDUN NURI JURNALI, 2025)
This article examines Uzbek somatic phraseological units containing the component “hair” (“soch”) as a linguocultural concept. Within the scope of the research, phraseologisms involving "hair" are analyzed as linguocultural tools that reveal semantic layers associated with national mentality, social values, and aesthetic perceptions. In these expressions, "hair" functions not only as a physical attribute but also as a symbolic representation of femininity, suffering, beauty, wisdom, and social status. The study applies a systematic approach to explore the semantic nuances and functional loads of these idioms in folk oral traditions. The findings highlight how Uzbek somatic phraseologisms reflect the people’s linguocultural worldview, aesthetic norms, and cultural stereotypes through expressive means.